Addressing Legal Uncertainty in Delayed Informed Consent: Protecting Health Workers in Indonesian Hospitals - Surianto Subu, Toto; Isrul, Muhammad; Syaban, Abdul Rahim; Noviati, Noviati; Hadju, Lodes (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
In Indonesia’s emergency settings, family requests to postpone medical procedures present significant legal risks for health workers. Medical records often capture only patient consent or refusal, neglecting documentation of deferred actions. This study analyzes the legal position of deferred informed consent under the Health Law, the Medical Practice Law, and Ministry of Health regulations, while exploring practices observed at a district hospital. Using a descriptive legal approach, normative analysis was combined with semi-structured interviews with nine participants at Aliyah 1 General Hospital, including the chair of the medical committee, a medical records officer, physicians, and ward heads. Findings highlight three recurring issues: role ambiguity (unclear disclosure responsibilities during busy periods), temporal opacity (uncertainty about decision-making time and its effect on care), and undefined clinical thresholds (absence of guidelines for escalation). Additional problems include inconsistent delegation notes, varying comprehension among family members, and inadequate documentation of communication with off-site decision-makers. To address these gaps, this study proposes a Deferral of Medical Action Form and a Deferred-Action Standard Operating Procedure (SOP). These tools would record the initiator and rationale for postponement, urgency or triage level, risk briefing, time-bound reassessment, and clear clinical triggers. They mandate physician-led disclosure, identification of interpreters if needed, maintenance of brief communication logs, and linkage to eventual consent or refusal notes. By transforming informal deferral requests into a structured, time-sensitive process, this model safeguards patient autonomy while ensuring timely and legally defensible medical care.